2018
DOI: 10.21307/jofnem-2018-040
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Root-Knot Nematode (Meloidogyne javanica) Infecting Hops (Humulus lupulus) in Florida, USA

Abstract: Humulus lupulus (Cannabaceae), commonly referred to as hops, are perennial, herbaceous climbing plants, native to temperate northern climates. Hops are cultivated for their strobiles or cones, which are often used for flavoring and aroma in food, tea, and beer (Almaguer et al., 2014). Because of the high demand for hops from the micro-brewing industry in the Tampa-St. Petersburg area, it has recently been introduced in Florida. The crop grows rapidly in the early spring to late summer. Plants reach a mature he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this study, plant-parasitic nematode species recovered from the root zone of hop planted in a Florida field soil included M. javanica, P. brachyurus, P. minor, B. longicaudatus, X. setariae/vulgare complex, M. xenoplax, and H. dihystera. With the exception of M. javanica (Brito et al, 2018), this is the first report of P. brachyurus, P. minor, B. longicaudatus, X. setariae/ vulgare complex, M. xenoplax, and H. dihystera in the rooting zone soil of hop plants in Florida. For all nematodes, percent identity was greater than 97% for the first five accession numbers in each BLAST search; however, only a single amplicon was sequenced per nematode species, thus restricting the power of this study to identify mixed-species populations within the hop yard.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In this study, plant-parasitic nematode species recovered from the root zone of hop planted in a Florida field soil included M. javanica, P. brachyurus, P. minor, B. longicaudatus, X. setariae/vulgare complex, M. xenoplax, and H. dihystera. With the exception of M. javanica (Brito et al, 2018), this is the first report of P. brachyurus, P. minor, B. longicaudatus, X. setariae/ vulgare complex, M. xenoplax, and H. dihystera in the rooting zone soil of hop plants in Florida. For all nematodes, percent identity was greater than 97% for the first five accession numbers in each BLAST search; however, only a single amplicon was sequenced per nematode species, thus restricting the power of this study to identify mixed-species populations within the hop yard.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, plant-parasitic nematode species recovered from the root zone of hop planted in a Florida field soil included M. javanica, P. brachyurus, P. minor, B. longicaudatus, X. setariae/vulgare complex, M. xenoplax, and H. dihystera. With the exception of M. javanica (Brito et al, 2018), this is the first report of P. of these nematodes from soil in the rooting zone of the hop cultivars may have been an artifact of the previous natural grass cover in the field prior to establishing the hop yard, or the ryegrass groundcover located between the planting rows, as opposed to direct parasitism of the hop roots. Our findings are in agreement with other studies which have also reported lesion and root-knot nematode parasitizing hop plants in significant numbers in the Pacific Northwest of United States (Maggenti, 1962;Hafez et al, 1992), albeit by more temperate climate nematode species (P. neglectus, P. thornei, and M. hapla) than the nematode species observed in this study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…There are reports of the occurrence of M. incognita in hops in Iran (Jamali et al, 2016), also presenting the typical symptom of root infestation. There have been reports of Meloidogyne javanica (Treub, 1885) Chitwood, 1949, causing damage to hops in Florida, USA and São Paulo, Brazil (Brito et al 2018;Nascimento et al 2020). Root-knot (Meloidogyne spp.)…”
Section: A B C D Ementioning
confidence: 99%
“…Roots of stunted plants showed a high number of galls ( Figure 5), and soil samples revealed large numbers of plant-parasitic nematodes, especially root-knot nematodes. The root-knot nematode species was identified as Meloidogyne javanica, the Javanese root-knot nematode, a very common species in Florida and a major pest of vegetables in the state (Brito et al, 2018). Except for a report on northern root-knot nematodes (Meloidogyne hapla) on hops from Sacramento County, California (Maggenti 1962), no other reports could be found on root-knot nematodes infecting hops in the United States or elsewhere.…”
Section: Nematodes On Hopsmentioning
confidence: 99%